Aposthonia Krauss, 1911 (Embioptera: Oligotomidae) from Thailand, with description of a new species - Poolprasert, Pisit; Sitthicharoenchai, Duangkhae; Butcher, Buntika Areekul; Lekprayoon, Chariya (Zootaxa, 2011)
Three embiid species of the genus Aposthonia Krauss (Oligotomidae) are recognized from Thailand (Aposthonia borneensis, A. ceylonica, A. problita sp. n.) and the new species is described. The distribution of the three species in Thailand is shown and keys to the males of 25 species of this genus and to females found in Thailand are provided.